Annual Plan 1999-2000 Administration of the Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1999)
Coconut is the major crop of the territory end agriculture the productive sector of the islands concert. The entire cultivable area in the territory is under coconut. There is no access for further expansion of area of crop. The production level by the end of VIII Five Year Plan will be at 27.5 Billion nuts or veer. The IX Five Year Plan give adequate thrust for increasing production and productivity of coconut. By the end of the Five Year Plan, the level of production in targeted at 30 Billion nuts and also the oil content by adding one per cent of the present level. The package approach for increasing production and productivity are ably discussed under the relevant schemes.
Planning Department Administration of the Union Territory of Lakshadweep